Hypertension Self Management Behavior and Achievement of Therapeutic Targets Grade 1 Essential Hypertension - Suci Khasanah; Didik Prapto Sasongko; Amin Susanto; Danang Tri Yudono; Pramesti Dewi (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2023)
Uncontrolled blood pressure in hypertension will increase the risk of cardiovascular disease. Hypertension Self-Management correlates with controlled blood pressure and correlates with blood pressure. The current study used the controlled parameter of blood pressure based on the classification of hypertension, with measurements at that time, it does not describe the type of hypertension studied and the extent to which the therapy target was achieved based on time. This research aims to determine the correlation of Hypertension Self-Management Behavior (HSMB) with Target Achievement of Essential Hypertension Therapy. The research design was correlational. Data collection using the HSMB Questionnaire, documentation of blood pressure for the last 3 months and blood pressure measurements in the fourth month. All respondents who met the criteria to be the research sample, namely as many as 34 respondents. Most of the respondents had good HSMB and SBP therapy targets achieved (41.2%) and DBP therapeutic targets were not achieved (58.8%). The results of the correlation test: HSMB with the achievement of TDS and TDD targets obtained p values of 0.475 and 1.000. There is no correlation between hypertension self-management behavior and the achievement of treatment targets for Grade 1 hypertension, both on systolic and diastolic blood pressure.